Valorização turística da oliveira em Saint-Rémy de Provence: entre a requalificação simbólica e a deturpação dos valores patrimoniais - Julie Deramond; Pauline Grison; Eric Triquet (Via@)
This article examines the place of the olive heritage and its products in the tourism promotion of Saint-Rémy de Provence. This Provencal town was chosen because it is located in a region which is famous for its olive groves. By studying the iconic discourse based on the use of images linked to the olive-growing heritage, the aim is to examine the hypothesis that the olive, olive oil and the olive tree have above all an emblematic value as symbols of Provence. Our aim is to show that they are used primarily for commercial and tourist purposes, as well as being witnesses to a claimed cultural identity.